Electrosynthesis of a Defective Indium Selenide with 3D Structure on a Substrate for Tunable CO2 Electroreduction to Syngas. Issue 6 (19th December 2019) - Yang, Dexin; Zhu, Qinggong; Sun, Xiaofu; Chen, Chunjun; Guo, Weiwei; Yang, Guanying; Han, Buxing
Abstract: Syngas (CO/H2 ) is a feedstock for the production of a variety of valuable chemicals and liquid fuels, and CO2 electrochemical reduction to syngas is very promising. However, the production of syngas with high efficiency is difficult. Herein, we show that defective indium selenide synthesized by an electrosynthesis method on carbon paper (γ‐In2 Se3 /CP) is an extremely efficient electrocatalyst for this reaction. CO and H2 were the only products and the CO/H2 ratio could be tuned in a wide range by changing the applied potential or the composition of the electrolyte. In particular, using nanoflower‐like γ‐In2 Se3 /CP (F‐γ‐In2 Se3 /CP) as the electrode, the current density could be as high as 90.1 mA cm −2 at a CO/H2 ratio of 1:1. In addition, the Faradaic efficiency of CO could reach 96.5 % with a current density of 55.3 mA cm −2 at a very low overpotential of 220 mV. The outstanding electrocatalytic performance of F‐γ‐In2 Se3 /CP can be attributed to its defect‐rich 3D structure and good contact with the CP substrate. Abstract : Flower power : Electrosynthesized flower‐like γ‐In2 Se3 with abundant defects and a 3D structure on carbon paper (F‐γ‐In2 Se3 /CP) shows outstanding performance for the electroreduction of CO2 to syngas.